The Impact of Monetary policy on Consumption and Investment in Jordan during (1989-2013) - KHASAWNEH, Malik Qasim (Journal of Economics Library, 2015)
Abstract. Monetary policy is one of the important monetary subjects that can evaluate the performance of the policy and its tools, recent development in financial markets in the past years led to changes in the behavior of countries monetary policies, concentrated to achieve stability in the price level by creating new ideas of how monetary policy affects the economy and its components through linking macroeconomic activities (private spending components) with nominal interest rate. This study aims to analyze and evaluate the impact of Jordanian monetary policy on consumption and investment spending during the period (1989-2013) to predict the impact of monetary policy and its instruments on real economic activities and inflation. The study finds that lending rate affects investment negatively but it does not affect consumption and real GDP in the short run. However, in the long run investment is affected by the co-movements occurred in consumption lending rate and lagged investment. Also, the study finds that real GDP is affected by the co- movements that occurred in real GDP and lending rate. Furthermore, domestic credit is affected by the co-movements that happened in domestic credit and lending rate. Keywords. Consumption, Error correction model, Investment, Lending rate, Monetary policy. JEL. E20, F22, O23.